Association between type of congenital heart disease with child growth and development status: A cross-sectional study in Medan, Indonesia - Amelia, Putri; Yosephine, Astrid G.; Tobing, Tina CL.; Savira, Maya; Viandy , Vincent; Inglin, Mark (Narra Sains Indonesia, 2023)
Congenital heart disease (CHD) is a congenital disorder primarily affecting newborns and children. Children with CHD have a greater risk of experiencing growth delays or disorders compared to healthy children. CHD also affects various aspects of a child’s development. The aim of this study was to determine the association of CHD types (cyanotic and acyanotic) with the growth and development status of children. A cross-sectional study was conducted among CHD patients at a national reference hospital in Sumatra, H. Adam Malik General Hospital in Medan, Indonesia. The children's growth status was assessed using the WHO growth chart, and the developmental condition was evaluated through the Denver Developmental Screening Test-II. Chi-squared test and Fisher’s exact test were used to assess the association between the type of CHD with growth and development status in children. Using a consecutive sampling method, a total of 53 individuals were included in this study. Almost half of CHD patients (48.1%) were within the age group of 0–2 years and more than half (61.1%) were girls. Acyanotic CHD (74.1%) was more prevalent than cyanotic CHD (25.9%), with ventricular septum defect (VSD) as the most common diagnosis. A total of 37% of children with CHD suffered from malnutrition, whereas the remaining 62.9% had good nutrition. The Denver Developmental Screening Test-II indicated that 81.4% of the children were normal, whereas 18.5% had developmental disorders. Our data suggested a significant association between cyanotic CHD and poor growth status in children based on weight-for-age, weight-for-length, and body mass index (BMI)-for-age. However, there was no association between the type of CHD and developmental status in children. This study highlights that the type of CHD is significantly associated with the growth status of children, but not with their developmental status.